3D printed foods-carbs from the lab for better health. Issue 4 (July 2022) - Singh, Jyoti; Kaur, Jaspreet; Rasane, Prasad; Kaur, Sawinder
Abstract : Purpose of review: The purpose of the review is to describe carbohydrate based 3D food printing technology in light of how it is affected by the use of various ingredients of ink and the properties associated with carbohydrate inks used for printing. Special focus is diverted to evaluate its effect on texture and corresponding health implications associated with carbohydrate based printed foods. Recent findings: The focus of 3D food printed products has revolved around texture modulation and carbohydrates are the best possible additives to achieve this modification. Carbohydrate based inks are used to design healthy texturized printed foods to provide various health benefits to consumer in addition to satisfy their aesthetic requirements. Other ingredients such as prebiotics and probiotics are major adjuncts that add value to these carbohydrates based 3D food printed foods and may have synergistic effects. Summary: Although much of the current attention is on texture modulation, health aspects of the foods naturally drive the future course of research associated with the carbohydrate based 3D food printed foods.